Soil Chemical Fertility In Garden Palma Instrument Standard Testing Center In Mapanget Sub-District Minahasa Utara District - Gorung, Angely S.; Rondonuwu, Jenny J.; Titah , Tilda (Soil and Environment Journal, 2024)
This study aims to determine the chemical fertility of the soil: pH, C-organic, N, and P, soil in the garden of the Mapanget Palm Plant Instrument Standard Testing Center, North Minahasa Regency. This research was conducted from March to May 2023, using a survey method to determine the sample points by "purposive sampling". Soil sampling at 4 different land locations with 5 sample points at each location with a depth of 0-50 cm, samples were taken using a soil drill. Soil samples were analyzed at the Ecophysiology Laboratory of the Standard Testing Center for Palm Instruments including pH (H2O and KCL), C-organic (spectrophotometer), Nitrogen (Kjedahl), and Phosphorus (Olsen). The data obtained were analyzed descriptively. Based on the results of research that had been carried out in the garden of the Standard Testing Institute for Palm Plantation Instruments, it showed that the nutrient content was classified as low to very low. To increase the aspect of soil fertility in the BPSI Experimental Garden, it is recommended that Palm trees add N (urea) fertilizer according to the dosage and add organic fertilizer to increase the C-organic element. Keywords: soil fertility, nutrients, pH, C-organic, nitrogen, and phosphors Abstrak Penelitian ini bertujuan untuk mengetahui kesuburan kimia tanah: pH, C-organik, N, dan P, tanah di kebun Balai Pengujian Standar Instrumen Perkebunan Sawit Mapanget, Kabupaten Minahasa Utara. Penelitian ini dilaksanakan pada bulan Maret sampai dengan Mei 2023, dengan menggunakan metode survei untuk menentukan titik sampel secara "purposive sampling". Pengambilan sampel tanah pada 4 lokasi lahan yang berbeda dengan 5 titik sampel pada setiap lokasi dengan kedalaman 0-50 cm, sampel diambil dengan menggunakan bor tanah. Sampel tanah dianalisis di Laboratorium Ekofisiologi Balai Pengujian Standar Instrumen Perkebunan Sawit meliputi pH (H2O dan KCL), C-organik (spektrofotometer), Nitrogen (Kjedahl), dan Fosfor (Olsen). Data yang diperoleh dianalisis secara deskriptif. Berdasarkan hasil penelitian yang telah dilakukan di kebun Balai Pengujian Standar Instrumen Perkebunan Sawit menunjukkan bahwa kandungan hara tergolong rendah sampai sangat rendah. Untuk meningkatkan aspek kesuburan tanah pada Kebun Percobaan BPSI, disarankan agar tanaman aren diberikan pupuk N (urea) sesuai dosis dan diberikan pupuk organik untuk meningkatkan unsur C-organik. Kata kunci: kesuburan tanah, unsur hara, pH, C-organik, nitrogen, dan fosfor